2015
DOI: 10.1007/s00374-015-1037-9
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of minimum soil tillage on abiotic soil properties and composition of microbial communities in a shallow Cambisol originated from fluvioglacial deposits

Abstract: A long-term field experiment was run for 12 years to evaluate the impact of minimum tillage (MT) compared to conventional mouldboard ploughing (CT) on soil chemical, physical and microbial properties in a shallow Cambisol formed over fluvioglacial deposits of Drava river in Slovenia. Significant differences between MT and CT were found in vertical distribution of soil organic C (SOC) and nutrients (total N and plant available potassium); under MT, concentrations decreased from the soil surface to the lower lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
(55 reference statements)
3
9
0
Order By: Relevance
“…Less tillage disturbance seems to impact the living conditions of soil organisms, as found by, e.g., Helgason, et al 42 who detected less bacterial stress markers in no-till soils, a higher microbial abundance in general and an altered microbial community composition. The latter has been widely found [43][44][45] and can be confirmed fully by measurements made in this trial, even with reduced instead of no tillage. We have found a constantly higher microbial biomass in both the 0-10 and 10-20 cm soil layers and a higher dehydrogenase activity in the topsoil over 15 years.…”
Section: Discussionsupporting
confidence: 85%
“…Less tillage disturbance seems to impact the living conditions of soil organisms, as found by, e.g., Helgason, et al 42 who detected less bacterial stress markers in no-till soils, a higher microbial abundance in general and an altered microbial community composition. The latter has been widely found [43][44][45] and can be confirmed fully by measurements made in this trial, even with reduced instead of no tillage. We have found a constantly higher microbial biomass in both the 0-10 and 10-20 cm soil layers and a higher dehydrogenase activity in the topsoil over 15 years.…”
Section: Discussionsupporting
confidence: 85%
“…Also, Dong et al (2017) have recently reported that NT practices markedly enhanced the abundance of Thaumarchaeota (previously a class of Crenarchaeota but now a novel phylum) in the topsoil after 22 years of no-tillage managements in Northern China. On the contrary, archaea were found not to be affected by the different forms of tillage practices in the experiment conducted by Kaurin et al (2015) who compared minimum tillage to conventional mouldboard ploughing. In no-tilled soil, physical disturbance is absent hence there is less soil aeration than in tilled soils and this may promote the growth of anaerobic microbes (Dorr de Quadros et al, 2012).…”
Section: Lefse Analysis Of Significantly Enriched Archaea Communitiesmentioning
confidence: 85%
“…It is widely accepted that no-till, residue retention, cover crops and crop rotations are conservation agriculture practices that protect soil, water, nutrients and increase microbial activity and biomass (Feng, 2003). However, varying research outcomes have been reported (Kaurin et al, 2015;Dong et al, 2017) making specific impacts of conservation agriculture practices on soil bacteria and archaea particularly complex to explain (Ng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Site details are given in Table 2 and summarised here as four arable and two grassland sites: Lusignan, Atlantic arable site in France, with rotations of grassarable (least intensive) and continuous arable (most intensive) (http://www.soere-acbb.com/index.php/fr/, Kunrath et al, 2014;Senapati et al, 2014); Scheyern, Continental arable site in Germany with long-term plots of minimum-tillage with small fertilisation (least intensive) and conventional tillage with large fertilisation (most intensive) as described by Zeitz. et al (2004); Moskanjci, Pannonian arable site in Slovenia, with long-term plots of minimum-tillage (least intensive) and conventional tillage (most intensive) according to Kaurin et al (2015); Castro Verde, Mediterranean arable site in Portugal, where the least intensive plots were grass-arable rotation with minimum tillage and no fertilisation and the most intensive plots were conventionally ploughed and fertilised, as described by Marta-Pedroso et al (2007); Yorkshire Dales, Atlantic grassland site in the UK, with paired plots of extensive and intensive grassland at three locations within the Yorkshire Dales National Park, as described by de Vries et al 2012; Hainich, Continental grassland site in Germany, with paired plots of extensive and intensive grassland as described by Fischer et al (2010).…”
Section: Selection Of Sites For Indicator Evaluationmentioning
confidence: 99%